ANALISIS PENDAPATAN PETANI SAGU DI KABUPATEN SERAM BAGIAN TIMUR (STUDI KASUS DI DESA DAWANG) - Timisela, Natelda R.; Tuankotta, Eriyati; Kembauw, Esther (AGRIBIOS, 2025)
As one of the largest producers of sago commodities in Maluku Province, East Seram Regency has the opportunity to increase production which of course has an impact on improving the welfare of sago farmers. This study aims to analyze the income of sago farmers by the community in Dawang Village, East Seram Regency. The research location is in Dawang Village, Teluk Waru District, East Seram Regency. Sampling was carried out using the Slovin formula, namely 113 samples. This study uses the Multiple Linear Regression analysis method. The results of the study showed that the production variables and sago price variables had a significant effect on the income of the Dawang village community, while the production cost variables and depreciation costs had a negative effect on the income of the Dawang village community. From this study, it can be concluded that the higher the production and price of sago, the higher the income of farmers.